The influence of habitat selection on Canada Goose Branta canadensis nest success on Akimiski Island, Nunavut, Canada - Gan, Stacey K.; Abraham, Kenneth F.; Brook, Rodney W.; Murray, Dennis L. (Wildfowl, 2019)
Predation avoidance is likely the foremost factor driving nest site selection among ground-nesting birds. The consequences of nest site selection were investigated on nest success for Canada Geese Branta canadensis breeding on Akimiski Island, Nunavut, Canada in 2010. Habitat features were measured at the scale of a nesting territory, at the nest site (n = 241), and at random locations for both scales. Compared with paired random locations, nests were more likely to be in woody vegetation located closer to water at the territory scale and had less lateral vegetative cover but taller vegetation nearer to the nest site. Geese did not select nesting locations in vegetation that provided maximum cover, but rather located nests in areas providing both concealment from predators and visibility for the nesting female to enable early predator detection. Assessing the effect of habitat attributes on nest success did not yield unambiguous results, with the most parsimonious model showing an increasing probability of nest success with increasing nest age alone. Although nest site selection was not random, we suggest that increasing parental investment and declining predation risk (not likely mutually exclusive) through the breeding season had more influence on Canada Goose nest success on Akimiski Island than did choice of specific habitat features or spacing of nests.